2015
DOI: 10.1186/s41065-015-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity of Tunisian caprifig (Ficus carica L.) accessions using simple sequence repeat (SSR) markers

Abstract: BackgroundThe common fig (Ficus carica L.) is a gynodioecious species with two sexual forms: male trees (caprifigs) with male and female flowers and female trees that produce only female flowers that will result in the edible fig syconium. In this study the genetic diversity of 20 Tunisian accessions of caprifig is analyzed using SSR markers previously developed for this crop.ResultsThe results revealed that the 13 pairs of primers used amplified a total of 37 alleles in the accessions studied. The number of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Aradhya et al (2010) reported that the number of alleles ranged from 4 (LMFC22, LMFC31 and LMF35) to 9 (LMFC30) with a mean of 4.9. Similar results were also obtained by Essid et al (2015) with 20 caprifig accessions that the number of alleles per locus ranged from 2 (LMFC32, LMFC15, LMFC21, LMFC31, LMFC18, LMFC27, LMFC23) to 6 (LMFC30). Thus, results from present study and previous demonstrated that LMFC30 produced the highest number of alleles per locus.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Aradhya et al (2010) reported that the number of alleles ranged from 4 (LMFC22, LMFC31 and LMF35) to 9 (LMFC30) with a mean of 4.9. Similar results were also obtained by Essid et al (2015) with 20 caprifig accessions that the number of alleles per locus ranged from 2 (LMFC32, LMFC15, LMFC21, LMFC31, LMFC18, LMFC27, LMFC23) to 6 (LMFC30). Thus, results from present study and previous demonstrated that LMFC30 produced the highest number of alleles per locus.…”
Section: Resultssupporting
confidence: 73%
“…A heterozygote excess (Ho>He) was observed for the LMFC15, LMFC31, LMFC18, LMFC27 loci whereas a heterozygote deficiency (Ho<He) was observed in LMFC24 and MFC2 loci in a study dealing with genetic variation of caprifigs (Essid et al, 2015). According to Giraldo et al (2008), for all SSRs except LMFC15 and LMFC21, Ho values were higher than the expected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, simple sequence repeat (SSR), conserved ortholog set II (COSII), characterized amplified region (SCAR), amplified fragment length polymorphism (AFLP), restriction site−associated DNA sequencing (RADseq), internal transcribed spacer (ITS), sequence-related amplified polymorphism (SRAP), intersimple sequence repeat (ISSR), and random amplified, microsatellite polymorphism (RAMP)-PCR markers have been applied in genetic diversity, population structure, morphological variation, phylogenetic inference, traceability, and cultivar/species identification and discrimination (Zhang et al, 2001(Zhang et al, , 2018Yin et al, 2005;Sze et al, 2008;Chung et al, 2009;Kwon et al, 2009;Levin et al, 2009;Zhao et al, 2010;Balasubramani et al, 2011;Liu et al, 2012Liu et al, , 2020bTripathi, 2013;Xin et al, 2013;Chen and Zhong, 2014;Wang et al, 2015a;Chen J. et al, 2017;McCulloch et al, 2020;Jung et al, 2021). SSR markers can be used for the detection of genetic polymorphisms of species, calculation of genetic relationships (genetic distance) between varieties, identification of cultivars, and even construction of genetic maps and QTL mapping with sufficient SSR markers Essid et al, 2015;Ibrahim et al, 2016;Thammina et al, 2017;Portis et al, 2018b). One hundred fifteen SSR and 12 ILP markers were applied to construct a genetic map with the F1 population (Hu, 2015).…”
Section: Genetic Marker Developmentmentioning
confidence: 99%